Navigating a toxic workplace - Mattice, Catherine (--For dummies., 2025)
"In this book, award-winning HR/organizational development strategist and author Catherine Mattice walks you through how employees, managers, and business leaders can take direct and immediate action to improve their workplaces. You'll learn specific skills to reduce disrespect, bullying, and harassment, and identify behaviors to protect your own well-being and turn around your toxic work environment."--Page [4] of cover.